A method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons

By coupling and deposition of carbon dioxide and low-carbon hydrocarbons under metal-supported molecular sieve templates, a high specific surface carbon material catalyst was prepared, which solved the problem of low carbon dioxide utilization efficiency in the prior art, and achieved the potential improvement in the production and catalytic fields of high-quality carbon species.

CN115999527BActive Publication Date: 2025-04-15DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211611535.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-04-15
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize carbon dioxide, which limits its application potential in the field of catalysis.

Method used

A high specific surface carbon material catalyst was prepared by coupling the carbon dioxide and low-carbon hydrocarbons under a metal-supported molecular sieve template. The method includes passing low-carbon hydrocarbons and CO2 mixture into the gas solid phase reactor for deposition treatment, and then removing the template, washing and drying, to obtain a carbon material with a high specific surface.

Benefits of technology

The high-value utilization of carbon dioxide is achieved, high-quality carbon species are produced, and carbon materials with specific structures are generated through the orientation of the molecular sieve template, which has enhanced its application potential in the catalytic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115999527B_ABST
    Figure CN115999527B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of carbon material preparation, and specifically relates to a method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons. A metal-supported molecular sieve is used as a template, and a low carbon hydrocarbon and CO2 mixed gas is introduced into a gas-solid phase reactor for deposition treatment, and then the template is removed, washed with water, and dried to obtain a carbon material. The prepared catalyst has the characteristics of controllable morphology and specific surface area, simple composition, and high-value utilization of carbon dioxide. By selecting different template molecular sieves, carbon materials with different morphologies can be directionally designed. The catalyst has high purity and rich pore structure, and has good catalytic application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon material preparation, and in particular relates to a method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons. Background Art

[0002] The traditional high-value utilization of carbon dioxide is mainly through hydrogenation to generate aromatics, reforming with low-carbon alkanes to generate synthesis gas (a mixture of carbon monoxide and hydrogen), and further supporting high-value-added products such as low-carbon olefins, aromatics, and oil products through Fischer-Tropsch reaction or OX-ZEO technology. In addition, certain technical means can be used to directly carbonize carbon dioxide to form carbon black, graphite carbon, ordered mesoporous carbon materials, etc. According to different types of carbon, it can be used in traditional industrial fields such as rubber, leather, lubricants, food, and sewage treatment, and can be further modified to be used as a catalyst in the field of catalysis.

[0003] In recent years, carbon materials have been widely used in the field of catalysis. Carbon materials themselves are relatively stable and usually have low activity. Functionalization treatments such as local hydroxylation, carboxylation, and heteroatom doping can provide more free electrons for the conduction band, thereby improving the conductivity of the material and increasing the possibility of further application in the field of catalysis. Therefore, the development and utilization of carbon materials has always been one of the important topics in the field of catalysis. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons. The prepared carbon material has a controllable morphology and specific surface area, simple composition, and realizes the high-value utilization of carbon dioxide.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] On the one hand, the present invention provides a method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons, wherein the carbon material catalyst is prepared by the following method:

[0007] Using metal-loaded molecular sieve as a template, a mixture of low-carbon hydrocarbons and CO2 is introduced into a gas-solid phase reactor for deposition treatment, and then the template is removed, washed with water, and dried to obtain a carbon material.

[0008] In the above technical solution, further, the low-carbon hydrocarbons include one or more of alkanes, alkenes, and alkynes in C1-C4.

[0009] In the above technical scheme, further, the metal in the metal-loaded molecular sieve includes one or more of Cr, Fe, Co, Ni, Cu, Mo, W, Ru, Rh, Pd, Ag, Au, and Pt, and the metal loading amount is 0.1-20wt.%.

[0010] In the above technical solution, further, the deposition treatment temperature is 500-1000°C, the pressure is 0.05-0.5MPa, and the air velocity is 1000-10000ml / g cat / h, and the deposition treatment time is 2-200h.

[0011] In the above technical solution, further, the method for removing the template is:

[0012] Use HF pickling soaking treatment to remove SiO2 and metal oxides, or first use NaOH / KOH solution treatment to remove SiO2, and then add acid soaking treatment to remove metal elements.

[0013] In the above technical solution, further, the HF concentration is 1-20%; the NaOH / KOH solution concentration is 0.1-10M.

[0014] Another aspect of the present invention provides a carbon material catalyst prepared by the above method, wherein the specific surface area of ​​the catalyst is 200-2000m 2 / g.

[0015] The beneficial effects of the present invention are:

[0016] (1) By coupling carbon dioxide with low-carbon hydrocarbons, high-value utilization of carbon dioxide can be achieved, producing high-quality carbon species;

[0017] (2) Through the template effect of molecular sieve materials, carbon materials with specific structures are generated in a directionally manner, such as ordered mesoporous carbon materials CMK-3, CMK-8, FDU-12, FDU-15, etc., which have good application examples in many fields such as environment, catalysis, and chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the BET result of the carbon material catalyst prepared in Example 1;

[0019] Figure 2 This is a scanning electron microscope image of the carbon material catalyst prepared in Example 1. DETAILED DESCRIPTION

[0020] The following embodiments are only intended to explain the present invention. The protection scope of the present invention should include the entire content of the claims and is not limited to the embodiments.

[0021] The raw materials used in the following examples are all conventional products that can be purchased commercially.

[0022] Example 1

[0023] A 20 wt.% Ni / SBA-15 catalyst was prepared by a conventional impregnation method. The specific process was as follows: 5 g SBA-15, 4.933 g nickel nitrate hexahydrate, and 50 ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 0.5 h to obtain a Ni / SBA-15 catalyst.

[0024] Take 5g of the prepared catalyst, introduce a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 850°C, and keep the pressure at normal pressure for 100h, then switch to Ar and cool down to collect the catalyst after the reaction;

[0025] The obtained catalyst was immersed and stirred in a 5M NaOH solution to remove the template. The treatment conditions were room temperature and the treatment time was 3 hours. Finally, the obtained system was centrifuged at a speed of more than 12,000 rpm to ensure that the supernatant had no obvious turbidity. 100 mL of 1M HNO3 was added and soaked for 3 hours. The supernatant was removed by centrifugation again, washed with water, and the above centrifugation-water washing process was repeated 3 times. The carbon material was dried at 120°C to obtain.

[0026] The measured specific surface area of ​​the carbon material is 745 m 2 / g( Figure 1 ), the catalyst morphology was verified by scanning electron microscopy ( Figure 2 ), which is consistent with the morphology of CMK-3 ordered mesoporous carbon material and has higher quality.

[0027] Example 2

[0028] A 20 wt.% Ni / SBA-15 catalyst was prepared by a conventional impregnation method. Specifically, 5 g of SBA-15, 4.933 g of nickel nitrate hexahydrate, and 50 ml of deionized water were mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 1.5 h to obtain the desired catalyst.

[0029] Take 5g of the prepared catalyst, and introduce a mixture of CO2, CH4, and NH3 (50ml / min: 50ml / min: 50ml / min) at 850°C, at normal pressure, for 100h, then switch to Ar and cool down to collect the catalyst after the reaction. The obtained catalyst was treated in a 5M NaOH solution at room temperature for 3h, and finally the obtained system was centrifuged at a speed of more than 12000 rpm to ensure that the supernatant had no obvious turbidity, and then 100mL of 1M HNO3 was added to soak for 3 hours, and the supernatant was removed by centrifugation again, washed with water, and the above centrifugation-washing process was repeated 3 times, and dried at 120°C to obtain a carbon material.

[0030] The measured specific surface area of ​​the carbon material catalyst is 518m 2 / g.

[0031] Example 3

[0032] A 10 wt.% Fe / ZSM-5 catalyst was prepared by a conventional impregnation method. Specifically, 5 g of SBA-15, 3.875 g of ferric nitrate nonahydrate, and 100 ml of deionized water were mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 0.1 h to obtain the desired catalyst.

[0033] Take 5g of the prepared catalyst, pass a mixture of CO2 and C2H6 (50ml / min: 50ml / min) at 500℃, continue to pass for 50h, the pressure is 0.5MPa, then switch to Ar and cool down to collect the catalyst after the reaction. The obtained catalyst is treated in a 5MNaOH solution at room temperature for 3h, and finally the obtained system is centrifuged at a speed of more than 12000 rpm to ensure that the supernatant has no obvious turbidity, then add 1MHNO3 100mL to soak for 3 hours, centrifuge again to remove the supernatant, wash with water, repeat the above centrifugation-water washing process 3 times, and dry at 120℃ to obtain the desired carbon material.

[0034] The measured specific surface area of ​​the carbon material catalyst is 601m 2 / g.

[0035] Example 4

[0036] A 10 wt.% NiFe / ZSM-5 catalyst was prepared by a conventional impregnation method. Specifically, 5 g ZSM-5, 2.465 g nickel nitrate hexahydrate, 3.875 g ferric nitrate hexahydrate, and 100 ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 0.5 h to obtain the desired catalyst.

[0037] Take 5g of the prepared catalyst, pass a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 900℃, continue to pass for 30h, normal pressure, then switch to Ar and cool down to collect the catalyst after the reaction. The obtained catalyst is treated in a 5M NaOH solution at room temperature for 3h, and finally the obtained system is centrifuged at a speed of more than 12000 rpm to ensure that the supernatant has no obvious turbidity, then add 1M HNO3100mL and soak for 3 hours, centrifuge again to remove the supernatant, wash with water, repeat the above centrifugation-water washing process 3 times, and dry at 120℃ to obtain the desired carbon material.

[0038] The measured specific surface area of ​​the carbon material catalyst is 435m 2 / g.

[0039] Example 5

[0040] A 10 wt.% Mo / ZSM-5 catalyst was prepared by a conventional impregnation method. Specifically, 5 g ZSM-5, 0.879 g hydrated ammonium molybdate, and 100 ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 550°C for 4 h, and carbonized with methane at 550°C for 30 min to obtain the desired catalyst.

[0041] Take 5g of the prepared catalyst and introduce CO2 and i-C4H 10 A mixed gas (50ml / min: 50ml / min) was continuously introduced for 10 hours at a pressure of 0.2MPa, and then switched to Ar and cooled to collect the catalyst after the reaction. The obtained catalyst was treated in a 20% HF solution at room temperature for 3 hours, and finally the obtained system was centrifuged at a speed of more than 12,000 rpm to ensure that the supernatant had no obvious turbidity, and then the supernatant was removed and washed with water, and the above centrifugation-water washing process was repeated 3 times, and dried at 120°C to obtain the desired carbon material.

[0042] The measured specific surface area of ​​the catalyst is 397 m 2 / g.

[0043] Example 6

[0044] A 0.5wt.% Pt / ZSM-5 catalyst was prepared by a conventional impregnation method. Specifically, 5g ZSM-5, 0.052g anhydrous chloroplatinic acid, and 100ml deionized water were mixed, stirred until dry, dried at 120°C, calcined at 550°C for 4h, and carbonized with methane at 550°C for 30 minutes to obtain the desired catalyst.

[0045] Take 5g of the prepared catalyst, pass a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 900°C for 100h, normal pressure, then switch to Ar and cool down to collect the catalyst after the reaction. The obtained catalyst is treated in a 20% HF solution at room temperature for 3h, and finally the obtained system is centrifuged at a speed of more than 12000 rpm to ensure that the supernatant has no obvious turbidity, then remove the supernatant, wash with water, repeat the above centrifugation-washing process 3 times, and dry at 120°C to obtain the desired carbon material.

[0046] The measured specific surface area of ​​the catalyst is 768 m 2 / g, has a higher specific surface area.

[0047] Example 7

[0048] A 5wt.% NiMo / MCM-22 catalyst was prepared by a conventional impregnation method. Specifically, 5g ZSM-5, 1.233g nickel nitrate hexahydrate, 0.513g ammonium heptamolybdate hydrate, and 100ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 550°C for 4h, and carbonized with methane at 550°C for 30min to obtain the desired catalyst.

[0049] Take 5g of the prepared catalyst, pass a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 900℃, continue passing for 100h, 0.5MPa, then switch to Ar and cool down to collect the catalyst after the reaction. Treat the obtained catalyst in a 20% HF solution at room temperature for 3h, and finally centrifuge the obtained system at a speed of more than 12000 rpm to ensure that the supernatant has no obvious turbidity, then remove the supernatant, wash with water, repeat the above centrifugation-washing process 3 times, and dry at 120℃ to obtain the desired carbon material.

[0050] The measured specific surface area of ​​the catalyst is 727 m 2 / g.

[0051] Example 8

[0052] A 20 wt.% Ni / SBA-15 catalyst was prepared by a conventional impregnation method. The specific process was as follows: 5 g SBA-15, 4.933 g nickel nitrate hexahydrate, and 50 ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 1 h to obtain a Ni / SBA-15 catalyst.

[0053] Take 5g of the prepared catalyst, introduce a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 850°C, and keep the pressure at normal pressure for 100h, then switch to Ar and cool down to collect the catalyst after the reaction;

[0054] The obtained catalyst was immersed and stirred in a 5M HF solution to remove the template. The treatment conditions were room temperature and the treatment time was 3 hours. Finally, the obtained system was centrifuged at a speed of more than 12,000 rpm to ensure that the supernatant had no obvious turbidity. The supernatant was removed and washed with water. The above centrifugation-water washing process was repeated 3 times and dried at 120°C to obtain a carbon material.

[0055] The measured specific surface area of ​​the carbon material is 709 m 2 / g.

[0056] Example 9

[0057] A 20 wt.% Fe / S-1 catalyst was prepared by a conventional impregnation method. The specific process was as follows: 5 g SBA-15, 4.933 g nickel nitrate hexahydrate, and 50 ml deionized water were uniformly mixed, stirred until dry, dried at 120°C, calcined at 800°C for 4 h, and reduced with hydrogen at 750°C for 1 h to obtain a Ni / SBA-15 catalyst.

[0058] Take 5g of the prepared catalyst, introduce a mixture of CO2 and CH4 (50ml / min: 50ml / min) at 900°C, and keep the pressure at normal pressure for 100h, then switch to Ar and cool down to collect the catalyst after the reaction;

[0059] The obtained catalyst was immersed and stirred in a 5M HF solution to remove the template. The treatment conditions were room temperature and the treatment time was 3 hours. Finally, the obtained system was centrifuged at a speed of more than 12,000 rpm to ensure that the supernatant had no obvious turbidity. The supernatant was removed and washed with water. The above centrifugation-water washing process was repeated 3 times and dried at 120°C to obtain a carbon material.

[0060] The measured specific surface area of ​​the carbon material is 591 m 2 / g.

Claims

1. A method for preparing a high specific surface carbon material catalyst by coupling carbon dioxide and low carbon hydrocarbons, characterized in that: The carbon material catalyst is prepared by the following method: Using metal-supported molecular sieve as a template, a mixture of low-carbon hydrocarbons and CO2 is introduced into a gas-solid phase reactor for deposition treatment, followed by removal of the template, water washing, and drying to obtain a carbon material catalyst; The low-carbon hydrocarbons are alkanes in the range of C1-C4; The metal in the metal-loaded molecular sieve is selected from one or more of Fe, Ni, Mo, Pt, Pd, Ru, Cr, and W, and the metal loading is 0.1-20wt.%; the molecular sieve is selected from one of SBA-15, ZSM-5, and MCM-22; The deposition treatment temperature is 500-1000°C, the pressure is 0.05-0.5MPa, and the air velocity is 1000-10000ml / g cat / h, the deposition treatment time is 2-200h; The method for removing the template is: immersion treatment with HF pickling or treatment with NaOH / KOH solution first and then acid immersion treatment.

2. The method according to claim 1, characterized in that The HF concentration is 1-20%; the NaOH / KOH solution concentration is 0.1-10M.

3. A carbon material catalyst prepared by the method according to any one of claims 1 to 2, characterized in that: The specific surface area of ​​the catalyst is 200-2000m 2 / g.

Citation Information

Patent Citations

  • Method using molecular sieve catalyst immobilized with gold to transform low-carbon hydrocarbon into aromatic hydrocarbon

    CN103159578A

  • Carbon material loaded cobalt-based catalyst as well as preparation and application thereof

    CN113996301A